Unlocking the potential of immersive technologies in higher education: A systematic review - Kamrozzaman, Nurul Aisyah; Jie, Amy Liew Xiu; Nayan, Noor Sahirah Md (International Journal of Innovative Research and Scientific Studies, 2025)
A wealth of literature confirms the benefits of immersive technologies in higher education; however, a critical barrier to scalable adoption remains the lack of comprehensive pedagogical frameworks and institutional support structures. This systematic review synthesizes not only learning outcomes but, more importantly, the instructional strategies and implementation challenges reported across thirty studies (2020–2025). Our analysis identifies a shift toward experiential and collaborative learning models, while highlighting a persistent deficit in formalized training and support for faculty. We argue that the primary challenge is no longer technological but pedagogical. The review’s contribution is a set of evidence-based principles for faculty development and pedagogical guidelines tailored to immersive learning, an essential step for sustainable integration.